MicroRNA-155: Regulation of Immune Cells in Sepsis. (8th January 2021) - Chen, Ming; Wang, Fuquan; Xia, Haifa; Yao, Shanglong
Abstract : MicroRNAs are small noncoding RNAs which regulate gene expression at the posttranscriptional level. miR-155 is encoded by the miR-155 host gene (miR155HG), also known as the noncoding B cell integration cluster (BIC). MicroRNAs are widely expressed in various hematopoietic cells and are involved in regulating the immune system. In this review, we summarized how miR-155 modulates specific immune cells and the regulatory role of miR-155 in sepsis. miR-155 is expressed by different populations of innate and adaptive immune cells and is involved in the regulation of development, proliferation, and function in these cells. Sepsis is associated with uncontrollable inflammatory responses, accompanied by unacceptably high mortality. Due to the inadequacy of diagnostic markers as well as treatment strategies, treating sepsis can be a huge challenge. So far, a large number of experiments have shown that the expression of miR-155 is increased at an early stage of sepsis and that this increase is positively correlated with disease progression and severity. In addition, by blocking the proinflammatory effects of miR-155, it can effectively improve sepsis-related organ injury, providing novel insights to identify potential biomarkers and therapeutic targets for sepsis. However, since most of the current research is limited to animal experiments, further clinical research is required to determine the function of miR-155 and its mechanism related to sepsis.